Root inoculation with Pseudomonas putida KT2440 induces transcriptional and metabolic changes and systemic resistance in maize plants - Planchamp, Chantal; Glauser, Gaetan; Mauch-Mani, Brigitte (Frontiers in Plant Science, 2015)
Pseudomonas putida KT2440 (KT2440) rhizobacteria colonize a wide range of plants. They have been extensively studied for their capacity to adhere to maize seeds, to tolerate toxic secondary metabolites produced by maize roots and to be attracted by maize roots. However, the response of maize plants to KT2440 colonization has not been investigated yet. Maize roots were inoculated with KT2440 and the local (roots) and systemic (leaves) early plant responses were investigated. The colonization behavior of KT2440 following application to maize seedlings was investigated and transcriptional analysis of stress- and defense-related genes as well as metabolite profiling of local and systemic maize tissues of KT2440-inoculated were performed. The local and systemic responses differed and more pronounced changes were observed in roots compared to leaves. Early in the interaction roots responded via jasmonic acid- and abscisic acid-dependent signaling. Interestingly, during later steps, the salicylic acid pathway was suppressed. Metabolite profiling revealed the importance of plant phospholipids in KT2440-maize interactions. An additional important maize secondary metabolite, a form of benzoxazinone, was also found to be differently abundant in roots three days after KT2440 inoculation. However, the transcriptional and metabolic changes observed in bacterized plants early during the interaction were minor and became even less pronounced with time, indicating an accommodation state of the plant to the presence of KT2440. Since the maize plants reacted to the presence of KT2440 in the rhizosphere, we also investigated the ability of these bacteria to trigger induced systemic resistance (ISR) against the maize anthracnose fungus Colletotrichum graminicola. The observed resistance was expressed as strongly reduced leaf necrosis and fungal development in infected bacterized plants compared to non-bacterized controls, showing the potential of KT2440 to act as resistance inducers.